Ecosystem services and landscape planning. How to integrate two different worlds in a high-density urban setting. - Wende, Wolfgang (Birkhäuser, 2019)
This chapter in-tends to offer a brief definition and theoretical and methodological concept of ecosystem services and the landscape planning approach, considering, in particular, a city-wide landscape policy level. The discussion encompasses the difficulties involved in integrating the ecosystem services concept into the legally embedded planning tools and planning practices accepted by various stakeholders, clients, and local authorities. One major problem is monetizing the value of ecosystems and their functions at a spatial level. The paper considers urban case studies from China and Germany to illustrate how ecosystem services and landscape planning can be integrated in high-density urban settings.
Keywords: Großstadt; Freiraumplanung; Landschaftsplanung; Ökosystem; Stadtklima; Stadtlandschaft; Naturschutz; Ökosystemdienstleistung